Émergence du modèle d’université entrepreneuriale : brèves notes critiques - Carlos Benedito Martins (Socio)
Supported by a relevant bibliography, the article addresses the construction of a specific conception of higher education, which was called a “business university” that seeks to establish a closer interaction with the economic field. This model has impacted the internal organization of the university, since the collegial administration of professors has been replaced by a body of managers who introduce values of efficiency and productivity in academic departments. This type of university has disseminated an ethos and a business mentality and culture not only among managers, but also among students and professors.